Circulating Haptoglobin and Metabolic Syndrome in Renal Transplant Recipients. Issue 1 (December 2017) - Minović, Isidor; Eisenga, Michele; Riphagen, Ineke; Berg, Else; Kootstra-Ros, Jenny; Frenay, Anne-Roos; Goor, Harry; Rimbach, Gerald; Esatbeyoglu, Tuba; Levy, Andy; Gaillard, Carlo; Geleijnse, Johanna; et al.
Abstract Haptoglobin (Hp) is an acute phase protein that has recently been linked to components of the metabolic syndrome (MetS). We aimed to evaluate Hp as marker of MetS, and to assess its association with long-term outcome in renal transplant recipients (RTR). We measured plasma Hp in a prospective cohort of 699 stable RTR and 149 healthy controls. Median plasma Hp concentration in RTR was 1.4 [interquartile range (IQR), 1.0–1.8] g/L, which was higher compared to 1.1 [0.9–1.4] g/L in controls (P < 0.001). Hp was independently associated with the MetS (β = 0.10) (P = 0.005). During follow-up of 5.4 [4.8–6.1] years, 150 (21%) recipients died, of whom 60 (9%) due to cardiovascular causes, and 83 (12%) RTR developed graft failure. High (≥2.0 g/L) and low (≤0.9 g/L) plasma Hp were associated with increased risk of mortality (HR's 2.3 [1.3–4.1] and 1.9 [1.0–3.5], resp.), predominantly cardiovascular. The association of high Hp lost significance upon adjustment for inflammation markers (HR 1.5 [0.8–2.7]), while low Hp was independently associated with mortality (HR 2.2 [1.2–4.0]). Hp was not associated with graft failure (P = 0.49). In conclusion, plasma Hp is independently associated with MetS in RTR. Importantly, high and low Hp are associated with increased mortality risk, independent of MetS.